Impact of the ‘Public Procurement Rules 2008’ on the implementation of construction projects - a case study on the public works department - Chakraborty, Ajay Kumar (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.